'Tension' and 'care' as cornerstones of criteria for poetic-visual inquiry as arts-based educational research. Issue 3 (1st December 2015) - Yuan, Yanyue; Hickman, Richard
This article aims to address a number of interrelated issues concerning criteria for arts-based research. We start by responding to current discussions and debates over criteria, with a tacit goal of redefining the nature and goal of emerging visions of doing qualitative-oriented research. After reviewing some emerging frameworks for judging qualitative-oriented research and arts-based studies, we explore the prospect of integrating poetic elements into visual inquiry. This feeds into our suggestion of poetic-visual inquiry as a form of arts-based research, which we elaborate through three existing studies. In relation to this, we raise tension and care as two keys for thinking through researchers' consciousness when carrying out arts-based research.